2003
DOI: 10.1002/bjs.4066
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative fasting

Abstract: Most patients having elective operations can be allowed a free intake of clear fluids up to 2 h before anaesthesia. Preoperative carbohydrates reduce postoperative insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
171
0
51

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(226 citation statements)
references
References 60 publications
4
171
0
51
Order By: Relevance
“…The medications used were also analyzed in this study, particularly atropine, due to their mechanisms of action that can cause a decrease in saliva and lead the patient to feel thirsty (12)(13)(14) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The medications used were also analyzed in this study, particularly atropine, due to their mechanisms of action that can cause a decrease in saliva and lead the patient to feel thirsty (12)(13)(14) .…”
Section: Discussionmentioning
confidence: 99%
“…The drugs used can also cause dryness of the oral mucosa in patients in the postoperative period (12,13) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One previous study administered the preoperative carbohydrate beverage to a group of type 2 diabetics and found that gastric emptying of the drink was the same -if not faster -than that of healthy controls, with a return to baseline blood glucose levels three hours after ingestion (90). It may be that gastric emptying of liquids remains relatively normal in these populations with alterations found only in the emptying of solids (91).…”
Section: Future Directionsmentioning
confidence: 97%
“…Patient hypovolemia may increase incidence of PONV and generous hydration or more liberal conduct regarding zero diet may ease these effects. (19) Inhalation anesthetics increase risk of PONV, mainly nitrous oxide. In studies with animals, this agent may alter the pressure of the middle ear and cause intestinal distension, besides activating the dopamine system.…”
Section: Preoperative Strategiesmentioning
confidence: 99%